Penerapan Teori Belajar Piaget Berbantuan Media Kantong Penjumlahan dalam Pembelajaran Matematika pada Peserta Didik Kelas I SDN Kedungpane 02 - Wisnu Aji Suryo Anggono; Dinda Suci Aisyah Fidayatullah; Siti Siyam Irma Imawati; Anisa Nuraeini; Irine Amalia Sinta Balqis; Haninda Cahya Ramadhani; Trimurtini T (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
One of the lessons at school is mathematics, especially at elementary school level. According to Piaget's learning theory, children aged 7 to 12 years are at a concrete operational stage of development. In mathematics learning, teachers are confused about using appropriate learning media so that students focus on the material, not just the media used. The aim of this research is to examine the application of Piaget's learning theory with the help of learning media of addition bags and number cards in mathematics learning related to the concept of adding numbers 1 to 20 for class I elementary school students at Kedungpane 02 State Elementary School. This research is a form of qualitative research that uses data collection techniques through observation, interviews, and documentation as well as data analysis techniques, namely descriptive qualitative. The research was conducted at Kedungpane 02 State Elementary School with the subjects involved were all class I students totaling 27 children and class teachers. Researchers provide solutions related to problems that arise in class by applying the PBL model assisted by adding bags and number cards. The results of the research show that the application of the addition bag media is effective in providing meaningful and in-depth concepts of addition material for class I students at SD Negeri Kedungpane 02.